Selective self-etherification of 5-(hydroxymethyl) furfural over Sn-Mont catalyst - Shinde, S; Rode, C (Catalysis Communications, 2017)
Sn-Mont was found to be a highly efficient catalyst for self-etherification of 5-(hydroxymethyl)furfural (HMF) to give 5,5'-oxy(bis-methylene)-2-furaldehyde (OBMF). L-B acidity of Sn(OH)(4) species enwrapped into the layers of montmorillonite was responsible for the excellent activity of Sn-Mont catalyst giving almost complete conversion of HMF with 98% selectivity to OBMF. Aprotic non-polar, dichloroethane was most effective solvent due to the facile formation of oxonium ion mediating etherification reaction. The catalyst showed suitable recyclability confirming its appreciable hydrolytic stability in water, and retention of its acidity.